Exploring Automata Theory with an Educational Activity Using Graph Grammar for K-12 Education - Silva, Júlia Veiga da; Silva Junior, Braz Araujo da; Cavalheiro, Simoné André da Costa; Foss, Luciana (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2024)
This paper proposes an educational activity for K-12 Education, aligned with the Brazilian National Common Curricular Base, which explores Automata Theory using Graph Grammar. Although several areas of computing are increasingly integrated into the educational context, the theoretical area is still neglected. Due to the scarcity of direct approaches in K-12 Education, this project seeks to bridge this gap. The proposed activity not only develops a specific National Common Curricular Base skill but also indirectly enhances Computational Thinking skills.